2005
DOI: 10.1159/000090335
|View full text |Cite
|
Sign up to set email alerts
|

Mild Hypothermia Ameliorates Lung Ischemia Reperfusion Injury in an ex vivo Rat Lung Model

Abstract: Background: Ischemia reperfusion (I-R) injury of the lung frequently occurs after cardiopulmonary bypass, pulmonary thromboendarterectomy, lung transplantation, and major pulmonary resection with vascular reconstruction. Mild hypothermia ameliorates ischemia reperfusion injury of the brain and the liver. However, the effect of mild hypothermia on I-R injury of the lung has not been investigated. Methods: The lungs of Lewis rats underwent 80 min of ischemia followed by 60 min of reperfusion in an ex vivo perfus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 34 publications
1
17
0
Order By: Relevance
“…and collagen matrix, hardening of blood vessels and increased resistance of the blood vessels; ii) hyperplasia and hypertrophy of the smooth muscle cell membrane, leading to intermembrane hypertrophy; and iii) loss of the muscular layer of the pulmonary arteriole (11). The present study demonstrated that silymarin significantly reduced lung I/R-induced pulmonary vascular dysfunction and lung moisture.…”
supporting
confidence: 57%
“…and collagen matrix, hardening of blood vessels and increased resistance of the blood vessels; ii) hyperplasia and hypertrophy of the smooth muscle cell membrane, leading to intermembrane hypertrophy; and iii) loss of the muscular layer of the pulmonary arteriole (11). The present study demonstrated that silymarin significantly reduced lung I/R-induced pulmonary vascular dysfunction and lung moisture.…”
supporting
confidence: 57%
“…Hypothermia has been shown to attenuate ischemia-reperfusion lung injury (Shoji et al, 2005;Zhang et al, 2006;Chang et al, 2008) and ventilator-induced lung injury (Lim, 2003a;Suzuki et al, 2004;Morita et al, 2009;Cruces et al, 2011;Aslami et al, 2012). Moreover, animal literature shows a consistent protective effect of hypothermia on toxin-induced lung injury (Lim, 2003b;Scumpia et al, 2004;Chin et al, 2007;Jo et al, 2011) and pneumonia .…”
Section: Introductionmentioning
confidence: 97%
“…39,40 Several experimental studies showed an attenuation in ischemia and reperfusion injury, in different organs (liver, lung, neuron), with hypothermia in different degrees. [17][18][19][20][21] Hypothermia was also used as a stimulating factor for the production of heat shock proteins, that showed a prophylactic protection of organ lesions including ischemia and reperfusion injury and acute pancreatitis. [41][42][43] Nevertheless, in clinical practice, some authors have found hyperamylasemia in hypothermic patients.…”
Section: Discussionmentioning
confidence: 99%
“…15,16 The ischemia and reperfusion injury has been also treated with hypothermia, and many authors have found an amelioration of the lesions in experimental studies. [17][18][19][20][21] Several studies have suggested that oxygen radicals play a role in a very early phase of AP, [22][23][24][25][26][27][28] and that the elevation of the pancreas oxidative status is related to the severity of the disease. 26,27 Exacerbated production of free oxygen radicals is related to the alteration of blood flow and to the ischemia/reperfusion phenomena.…”
Section: Introductionmentioning
confidence: 99%